Frank Miller's Daredevil and the ends of heroism - Young, Paul, 1968- (Comics culture., 2016)
In the late 1970s and early 1980s, writer-artist Frank Miller turned Daredevil from a tepid-selling comic to an industry-wide success story, then left to establish a renowned and controversial career. A childhood fan of the comic, media scholar Paul Young presents a rigorous study of the artist's influences and innovations, an examination of how Miller's vision impacted the comics industry, and a reflection on how Daredevil taught him about the creative possibilities of comics while shaking his faith in superheroes.